Magnetic characterization of cobalt nanowires and square nanorings fabricated by focused electron beam induced deposition - Venturi, Federico; Gazzadi, Gian Carlo; Tavabi, Amir H.; Rota, Alberto; Dunin-Borkowski, Rafal E.; Frabboni, Stefano (Beilstein Journal of Nanotechnology, 2018)
The magnetic properties of nanowires (NWs) and square nanorings, which were deposited by focused electron beam induced deposition (FEBID) of a Co carbonyl precursor, are studied using off-axis electron holography (EH), Lorentz transmission electron microscopy (L-TEM) and magnetic force microscopy (MFM). EH shows that NWs deposited using beam energies of 5 and 15 keV have the characteristics of magnetic dipoles, with larger magnetic moments observed for NWs deposited at lower energy. L-TEM is used to image magnetic domain walls in NWs and nanorings and their motion as a function of applied magnetic field. The NWs are found to have almost square hysteresis loops, with coercivities of ca. 10 mT. The nanorings show two different magnetization states: for low values of the applied in-plane field (0.02 T) a horseshoe state is observed using L-TEM, while for higher values of the applied in-plane field (0.3 T) an onion state is observed at remanence using L-TEM and MFM. Our results confirm the suitability of FEBID for nanofabrication of magnetic structures and demonstrate the versatility of TEM techniques for the study and manipulation of magnetic domain walls in nanostructures.
Keywords: focused electron beam induced deposition; magnetic force microscopy; magnetic nanostructures; off-axis electron holography; transmission electron microscopy

(untitled) - Chou, S. Y.; Wei, M. S.; Krauss, P. R.; Fischer, P. B. (J. Appl. Phys., 1994)

(untitled) - Chappert, C.; Fert, A.; Van Dau, F. N. (Nat. Mater., 2007)

(untitled) - Daughton, J. M. (Thin Solid Films, 1992)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belic, D.; Bertagnolli, E. (ACS Nano, 2013)

(untitled) - Gabureac, M.; Bernau, L.; Utke, I.; Boero, G. (Nanotechnology, 2010)

(untitled) - Parkin, S. S. P.; Hayashi, M.; Thomas, L. (Science, 2008)

(untitled) - Parkin, S. S. P.; Yang, S.-H. (Nat. Nanotechnol., 2015)

Physics of Ferromagnetism - Chikazumi, S. (Oxford University Press, 1997)

Nanofabrication Using Focused Ion and Electron Beams: Principles and Applications - Utke, I.; Moshkalev, S.; Russell, P. (Oxford University Press, 2012)

(untitled) - Schirmer, M.; Walz, M.-M.; Vollnhals, F.; Lukasczyk, T.; Sandmann, A.; Chen, C.; Steinrück, H.-P.; Marbach, H. (Nanotechnology, 2011)

(untitled) - Winhold, M.; Schwalb, C. H.; Porrati, F.; Sachser, R.; Frangakis, A. S.; Kämpken, B.; Terfort, A.; Auner, N.; Huth, M. (ACS Nano, 2011)

(untitled) - De Teresa, J. M.; Fernández-Pacheco, A.; Córdoba, R.; Serrano-Ramón, L.; Sangiao, S.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Fernandez-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

Introduction to magnetic materials - Cullity, B. D.; Graham, C. D. (Wiley, 2009)

Magnetic Nano- and Microwires - Design, Synthesis, Properties and Applications - Jamet, S.; Rougemaille, N.; Toussaint, J. C.; Fruchart, O. (Head-to-head domain walls in one-dimensional nanostructures: An extended phase diagram ranging from strips to cylindrical wires, 2015)

(untitled) - Grujicic, D.; Pesic, B. (J. Magn. Magn. Mater., 2005)

(untitled) - Zhu, J.-G.; Zheng, Y.; Prinz, G. A. (J. Appl. Phys., 2000)

(untitled) - Porro, J. M.; Berger, A.; Grimsditch, M.; Metlushko, V.; Ilic, B.; Vavassori, P. (J. Appl. Phys., 2012)

(untitled) - Jaafar, M.; Iglesias-Freire, O.; Serrano-Ramon, L.; Ibarra, M. R.; De Teresa, J. M.; Asenjo, A. (Beilstein J. Nanotechnol., 2011)

(untitled) - Jaafar, M.; Serrano-Ramón, L.; Iglesias-Freire, O.; Fernández-Pacheco, A.; Ibarra, M. R.; De Teresa, J. M.; Asenjo, A. (Nanoscale Res. Lett., 2011)

(untitled) - Rodríguez, L. A.; Magén, C.; Snoeck, E.; Serrano-Ramón, L.; Gatel, C.; Córdoba, R.; Martínez-Vecino, E.; Torres, L.; De Teresa, J. M.; Ibarra, M. R. (Appl. Phys. Lett., 2013)

(untitled) - Rodríguez, L. A.; Magén, C.; Snoeck, E.; Gatel, C.; Marín, L.; Serrano-Ramón, L.; Prieto, J. L.; Muñoz, M.; Algarabel, P. A.; Morellon, L.; De Teresa, J. M.; Ibarra, M. R. (Ultramicroscopy, 2013)

(untitled) - Gazzadi, G. C.; Frabboni, S. (Beilstein J. Nanotechnol., 2015)

(untitled) - Chapman, J. N.; Waddell, E. M.; Batson, P. E.; Ferrier, R. P. (Ultramicroscopy, 1979)

Electron Microscopy in Materials Science - Wade, R. H. (Some aspects of Lorentz microscopy, 1971)

(untitled) - Fuller, H. W.; Hale, M. E. (J. Appl. Phys., 1960)

(untitled) - Gabor, D. (Nature, 1948)

Advances in Imaging and Electron Physics - Pozzi, G. (Electron holography of long-range electromagnetic fields: A tutorial, 2002)

(untitled) - Völkl, E.; Allard, L. F.; Frost, B. (J. Microsc., 1995)

(untitled) - Tonomura, A.; Matsuda, T.; Endo, J.; Arii, T.; Mihama, K. (Phys. Rev. B, 1986)

Electron Energy-Loss Spectroscopy in the Electron Microscope - Egerton, R. F. (Springer, 2011)

(untitled) - Belova, L. M.; Dahlberg, E. D.; Riazanova, A.; Mulders, J. J. L.; Christophersen, C.; Eckert, J. (Nanotechnology, 2011)

(untitled) - Córdoba, R.; Sesé, J.; De Teresa, J. M.; Ibarra, M. R. (Microelectron. Eng., 2010)

(untitled) - Van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Dunin-Borkowski, R. E.; Kasama, T.; Wei, A.; Tripp, S. L.; Hytch, M. J.; Snoeck, E.; Harrison, R. J.; Putnis, A. (Microsc. Res. Tech., 2004)

(untitled) - Pablo-Navarro, J.; Sanz-Hernández, D.; Magén, C.; Fernández-Pacheco, A.; de Teresa, J. M. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Pablo-Navarro, J.; Magén, C.; de Teresa, J. M. (Nanotechnology, 2016)

(untitled) - Grillo, V.; Harvey, T. R.; Venturi, F.; Pierce, J. S.; Balboni, R.; Bouchard, F.; Gazzadi, G. C.; Frabboni, S.; Tavabi, A. H.; Li, Z.-A.; Dunin-Borkowski, R. E.; Boyd, R. W.; et al. (Nat. Commun., 2017)

(untitled) - Volkov, V. V.; Crew, D. C.; Zhu, Y.; Lewis, L. H. (Rev. Sci. Instrum., 2002)

(untitled) - Lohe, M. A. (Phys. Rev. D, 1979)

(untitled) - Nikulina, E.; Idigoras, O.; Vavassori, P.; Chuvilin, A.; Berger, A. (Appl. Phys. Lett., 2012)

(untitled) - Vavassori, P.; Grimsditch, M.; Novosad, V.; Metlushko, V.; Ilic, B. (Phys. Rev. B, 2003)

(untitled) - Franken, J. H.; van der Heijden, M. A. J.; Ellis, T. H.; Lavrijsen, R.; Daniels, C.; McGrouther, D.; Swagten, H. J. M.; Koopmans, B. (Adv. Funct. Mater., 2014)

(untitled) - Fernandez-Pacheco, A.; De Teresa, J. M.; Szkudlarek, A.; Córdoba, R.; Ibarra, M. R.; Petit, D.; O’Brien, L.; Zeng, H. T.; Lewis, E. R.; Read, D. E.; Cowburn, R. P. (Nanotechnology, 2009)